Children-in-law and Conflictual Dynamics in the Business Family - Ferrari, Filippo (European Journal of Family Business, 2025)
This study explores the emotional and relational experiences of in-laws in family businesses—an under-researched area in the family business literature. Drawing on Social Identity Theory (SIT), the research investigates whether in-laws working in Italian family SMEs experience a recurring pattern of perceived exclusion, identity frustration, and career dissatisfaction. Based on survey data collected from 158 in-laws working in Italian family firms, the study identifies a multifactorial configuration comprising five interrelated factors: perceived unfair treatment by the founder and siblings-in-law, identity frustration, career dissatisfaction, and intention to leave the family business. These factors are significantly and positively correlated, and all are negatively associated with self-categorization as a family member. Gender differences also emerged, with sons-in-law reporting higher frustration and stronger self-categorization compared to daughters-in-law. By applying SIT to intra-family dynamics, this study extends existing theory to examine how ambiguous identity and group membership shape in-law experiences. The findings highlight the need for more inclusive governance and integration strategies in family firms to prevent disengagement and conflict.